To calculate: To convert the radical expression sqrt[3]{x^{6} y^{9}} to rational exponent form and simlify.

Efan Halliday 2021-03-07 Answered
To calculate:
To convert the radical expression 3{x6 y9} to rational exponent form and simlify.
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

Brighton
Answered 2021-03-08 Author has 103 answers
Calculation:
According to exponential rules, n{a}=a1n
Given 3{x6 y9}
Applying the above rule: where a=x6 y9, n=3
3{x6 y9}=(x6 y9)13
According to product rule, (ab)n=an  bn
Applying the above rule: where a=x6, b=y9, n=13
3{x6 y9}=(x6)13 (y9)13
According to the power rule, (am)n=amn
Applying the above rule:
3{x6 y9}=x(6)(13) y(9)(13)
3{x6 y9}=x2 y3
Not exactly what you’re looking for?
Ask My Question
Jeffrey Jordon
Answered 2021-10-27 Author has 2047 answers

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more